Strategi Business Communication dalam Memperkuat Corporate Image PT Dahana pada Industri Tambang, Minyak dan Gas - Fauriana, Tafuzi; Amiruddin Saleh, MS; Hamzah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores business communication strategies for sustaining public trust in strategic industries, focusing on PT Dahana in the explosives sector. It analyzes PT Dahana’s practices using Excellence Theory, emphasizing the two-way symmetrical model, and identifies supporting and inhibiting factors. A qualitative method employed observation, interviews, and documentation. Findings reveal two-way communication via cross-unit coordination, interactive digital media, and responsiveness/transparency, fostering stakeholder relationships and issue management. PT Dahana’s strategy aligns with an effective symmetrical model enhancing public engagement. Recommendations: boost digital capacity, promote open internal culture, and expand accessible educational content.